On the parametric eigenvalue behavior of matrix pencils under rank one perturbations. Issue 1 (October 2016) - Gernandt, Hannes; Trunk, Carsten
Abstract: We study the eigenvalues of rank one perturbations of regular matrix pencils depending linearly on a complex parameter. We prove properties of the corresponding eigenvalue sets including a convergence result as the parameter tends to infinity and an eigenvalue interlacing property for real valued pencils having real eigenvalues only. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)